2022
DOI: 10.1155/2022/7550792
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Model Construction of College Students’ Entrepreneurial Ability Cultivation in Mental Health Education Environment

Abstract: National policies have been very supportive of college students as a new force in IEE (innovation and entrepreneurship education). Universities across the nation have increased their emphasis on entrepreneurship education and put a lot of effort into developing and enhancing college students’ EA (entrepreneurship ability). An important challenge facing universities is how to develop the psychological quality of IEE in college students and create a long-term training system. The author develops the EA evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the entrepreneurial education for college students in the new era, Bayesian statistics offers a powerful toolkit for enhancing both methods and abilities [11]. Bayesian inference, a cornerstone of this statistical framework, enables students to make decisions in the face of uncertainty by combining prior knowledge with new evidence in a principled manner [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the entrepreneurial education for college students in the new era, Bayesian statistics offers a powerful toolkit for enhancing both methods and abilities [11]. Bayesian inference, a cornerstone of this statistical framework, enables students to make decisions in the face of uncertainty by combining prior knowledge with new evidence in a principled manner [12].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%